partialCI: An R package for the analysis of partially cointegrated time series - Matthew Clegg; Christopher Krauss; Jonas Rende (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institute for Economics, 2017)
Partial cointegration is a weakening of cointegration, allowing for the residual series to contain a mean-reverting and a random walk component. Analytically, the residual series is described by a partially autoregressive process. The partialCI package provides estimation, testing, and simulation routines for PCI models in state space. We illustrate the functionality with two examples: A financial application in the context of pairs trading and a macroeconomic application, i.e., the relationship between GDP and consumption. For both examples, we show that the variables are not cointegated in the classic sense, but can be modeled with partial cointegration.
Keywords: 330; R software; cointegration; partial cointegration; pairs trading; permanent components; transient components